(untitled) (Bangladesh Journal of Botany, 2010)
Normal looking plants of Ornithogalum virens L. (Liliaceae) raised from γ-ray irradiated seeds were partially sterile. Meiotic studies carried out on this plant for two consecutive years revealed the frequent occurrence of a dicentric chromosome bridge accompanied by an acentric fragment at anaphase I (AI). Paracentric inversion followed by crossing over in the inverted region might have resulted in this type of consequence at AI. Normal plants of O. virens (2n = 6) showed regular presence of 3 bivalents at metaphase I (MI) and equal 3 : 3 separation of chromosomes at AI. Presence of 2 to 6 univalents in the pollen mother cells (PMCs) of the treated plant indicated the occurrence of occasional asynapsis possibly due to induced inversion. Early movement, lagging and unequal separations of chromosomes were encountered rather infrequently at AI. Pollen sterility of this inversion heterozygote plant was 44.80 and 54.64% in the first and second year, respectively compared to only 1.12 to 3.90% in the control plants. Key words: Ornithogalum virens; γ-ray; Paracentric inversion; Heterozygote; Sterility DOI: 10.3329/bjb.v38i1.5116 Bangladesh J. Bot. 38(1): 33-37, 2009 (June)